PENGARUH PENDAPATAN NELAYAN TERHADAP KESEJAHTERAAN MASYARAKAT DESA BELUNGKUR DALAM PERSPEKTIF ISLAM DI KECAMATAN LINGGA TIMUR KABUPATEN LINGGA - hartoto; Masjunaidi; Nova Samsidinarty (STAI Miftahul Ulum Tanjungpinang, 2023)
This article reviews the influence of fishermen’s income on the welfare of the Belungkur Village community in an Islamic perspective in Lingga Timur District, Lingga Regency. This study aims to determine the effect of fishermen’s income on the welfare of the Belungkur Village community in an Islamic Perspective in Lingga Timur District, Lingga Regency.And the community’s efforts to improve welfare. This type of research. The research instruments used were observation, questionnaires, interviews and documentation. The data in this study are primary data and secondary data. Primary data was obtained by distributing questionnaires to 32 respondents while secondary data was obtained from agencies related to research. The population in this study were 157 fishermen using simple random sampling technique, the number of sample taken in this study were 32 respondents. The data were analyzed using the Wilconxon test and processed using the Statistics Product and Service Solution (SPSS) version 25. The results of the study show that the income of fishermen has a positive and significant effect on the welfare of the community.